The role of artificial intelligence technologies in reducing crime rates in the UAE community - Almesafri, Aaesha; Alsuwaidi, Sharifa (Al-Adab Journal, 2025)
The study aimed to identify the mechanisms of reducing the crime rate within the UAE community using artificial intelligence techniques in the country from the viewpoint of security personnel. The study also aimed to identify the degree of application of artificial intelligence techniques in the UAE to reduce the crime rate within the UAE society from the point of view of personnel security and to study the effect of applying artificial intelligence techniques to reduce the crime rate within the UAE society from the viewpoint of security personnel. In order to achieve the objectives of the study, a descriptive and analytical approach was followed by preparing a questionnaire on the sector managers and their assistants in the Ministry of Interior sector in the UAE. Interview questions were also prepared to target a sample of managers in the Ministry of Interior sector in the UAE. For the purposes of this study, a non-probability objective sample was used consisting of (326) workers in the Ministry of Interior sector in the UAE, from sector managers and their assistants in the branches related to the topic of artificial intelligence and its role in reducing crime rates. As for the study sample of interviews, only interviews were conducted with (21) interviews due to the nature of managers ’work and their preoccupation in many cases.Among the most important findings of the study, the results of the study revealed that the application of artificial intelligence techniques in the UAE has a strong role in reducing the crime rate within the UAE society from the point of view of security personnel.